Longer-term effects of early childhood education and care: Evidence and policy - Melhuish, E; Tradução, M (2013)
In recent decades there has been an accumulation of evidence linking children's experience of early childhood education and care with longer-term child development outcomes. The provision of early childhood education and care is dependent upon the social and economic context of a country, which leads to great diversity between countries in the policy adopted. International evidence is used to show the longer-term benefits that result from good quality early childhood education and care, with particular emphasis on evidence from the UK. The evidence shows that benefits exist for social, cognitive and educational development and have consequences not only for individual but also for the wider society. International evidence indicates that good quality early education and care is an essential part of the infrastructure for longer term development in a modern state.